Hurricane season - Melleby, Nicole (Algonquin Young Readers, 2019)
Fig tries to connect with her artistic, bipolar father, after an incident at school leads her art teacher calls social services. She then researches the artist Van Gogh to try to understand the links between mental illness and creativity in an effort to better understand her father. Her new neighbor, Mark, understands more than Fig does about issues beyond bipolar disorder that plague her father, and he becomes indispensable to the family. Fig suffers drama at school too as she deals with a boy who likes her and the girl she has a crush on.